Perlindungan Hukum Terhadap Konsumen PDAM Kabupaten Belu Ditinjau dari Undang-Undang Nomor 8 Tahun 1999 Tentang Perlindungan Konsumen di Kota Atambua - Lay Rade, Jericho Gerald; Usman, Siti Ramlah; Dju Bire, Chatryen M. (Artemis Law Journal, 2025)
This study examines the legal protection of consumers of the Regional Drinking Water Company in Belu Regency, Atambua City, based on Law Number 8 of 1999 on Consumer Protection. Based on these issues, this study focuses on two main aspects: (1) how consumer protection for PDAM consumers in Atambua City is regulated under consumer protection law, and (2) the inhibiting factors that hinder the optimal implementation of legal protection for Regional Drinking Water Company consumers in Atambua City.This study employs an empirical juridical research method with a statutory and conceptual approach. Data were obtained through observation, interviews, and literature studies. The research findings indicate that although consumer protection law provides a legal foundation for consumer protection, its implementation in practice remains suboptimal. Several major obstacles include a lack of information transparency, infrastructure limitations, slow responses to consumer complaints, and weak government oversight. Therefore, improving transparency, enhancing infrastructure, and strengthening supervision and policy implementation are necessary to enhance consumer protection in Atambua City.